Insomnia Mental Health Issues Pandemic Covid-19 - Samsiah Jayos; Lau Ngie Hing; Aima Aimaduddin Bin Bollhasan (Psycho Idea, 2022)
Insomnia is one of the major sleep disorders that faced by people which lead to mental health issues. Inability to get enough amount of sleep that can causing difficulty to function during the daytime. This study is in purpose to determine the understanding of insomnia and awareness in public. Researchers using a qualitative approach to addresses the issue of insomnia and 5 respondents randomly picked to participate in a semi-structured interview to share their information about this issue. The data were based on the researcher’s observations throughout the field study and the data recorded from the interviews were then transcribed and analyzed using NVivo software to subsequently form themes and suitable sub-themes. Through all the interviews, data was analyzed and discusses four (4) themes that emerged from the information which are include 1.Symptoms of Insomnia, 2. Effects of Insomnia, 3.Factors of Insomnia and 4. Ways to handle Insomnia. This study provide additional information about the mental health problem known as insomnia. It includes the symptoms of insomnia, effects of insomnia, factors of insomnia and also provide the ways to handle insomnia. In conclusion, insomnia can leads to a lot of serious mental health problem such as depression, anxiety, easily frustrated and so on and this in turn would really be a serious problem as it could leads to people committing suicide if they are not cured in time especially during pandemic Covid-19